2011
DOI: 10.1038/onc.2011.97
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-like growth factor binding protein 5 suppresses tumor growth and metastasis of human osteosarcoma

Abstract: Osteosarcoma (OS) is the most common primary malignancy of bone. There is a critical need to identify the events that lead to the poorly understood mechanism of OS development and metastasis. The goal of this investigation is to identify and characterize a novel marker of OS progression. We have established and characterized a highly metastatic OS subline that is derived from the less metastatic human MG63 line through serial passages in nude mice via intratibial injections. Microarray analysis of the parental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
138
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(146 citation statements)
references
References 38 publications
7
138
1
Order By: Relevance
“…In this instance, the cooperation between c-Src and STAT3 could delay osteoblast differentiation with a positive feedback between IL-6 and c-Src pathways. Consistent with our model, we demonstrated that IL-6 enhances the expression of Igfbp5, which has been described to have important roles in bone physiology and pathology [19][20][21][22] . Interestingly, we found that IGFBP5 directly induced c-Src activation without affecting IGF-1 receptor phosphorylation.…”
Section: Discussionsupporting
confidence: 89%
“…In this instance, the cooperation between c-Src and STAT3 could delay osteoblast differentiation with a positive feedback between IL-6 and c-Src pathways. Consistent with our model, we demonstrated that IL-6 enhances the expression of Igfbp5, which has been described to have important roles in bone physiology and pathology [19][20][21][22] . Interestingly, we found that IGFBP5 directly induced c-Src activation without affecting IGF-1 receptor phosphorylation.…”
Section: Discussionsupporting
confidence: 89%
“…The involvement of IGFBPs in cancer is not fully understood, but there are reports suggesting that down-regulation of these proteins correlates with cancer progression (28)(29)(30)(31). Fig.…”
Section: Validation Of Differentially Expressed Genes On the Protein mentioning
confidence: 99%
“…For example, IGFBP-5 expression has recently been shown to be associated with increased survival times in breast cancer patients as well as being responsible for maintaining sensitivity to tamoxifen (Ahn et al , 2010). In addition, overexpression of IGFBP-5 in MCF-7 xenografts inhibited tumour development in mice (Ahn, Elwi, 2010) whilst recent studies have demonstrated a tumour suppressor role for IGFBP-5 in ovarian cancer cells (Rho et al , 2008) in osteosarcoma (Su et al , 2011) and in breast cancer after foetal alcohol exposure (Polanco et al , 2010). An intriguing relationship between IGFBP-5 and tumour dormancy has also been described.…”
Section: Igfbp-5 and Cancermentioning
confidence: 99%